FUNCTIONING AND VERBALIZATION OF THE CONCEPT «MIRACULOUS» IN THE NEWSPAPER DISCOURSE IN THE RUSSIAN AND ENGLISH LANGUAGES - Nikitina, J.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article analyzes such a linguistic-cognitive phenomenon as a concept pertaining to the newspaper discourse, to be more precise, the functioning of the concept «miraculous» in newspaper headlines. The results of comparative analysis of cognitive features and verbalization of the concept under study in the Russian and English cultural traditions in the frame of modern Russian and British media are presented. There are no fixed concepts. Over time, their content and structure change, correlating with changes in the reality. The media reflect most quickly to these changes, primarily by headlines. Having lost faith in miracles and the "miraculous phenomena" (religion for many people has become just a ritual, space flights have turned into ordinary events for science, the creation of a vaccine against coronavirus is an expected event) and using this adjective and its synonyms to describe ordinary phenomena that have nothing to do with a miracle, we have leveled its meaning. And it is quite clear that in the headlines of newspapers, especially British ones, as the study showed, the main nominee of this concept, the lexeme «miracle / miraculous» is almost not verbalized. These results may indicate a change in the world picture of representatives of the Russian and English cultures.